DEVELOPMENT OF LACTIC ACID FERMENTED BEVERAGE MADE FROM THE EXTRACT OF BROWN RICE AND MUNGBEAN MIXTURE - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Cool and hot water extraction procedure were examined for their suitability to yield desirable rice-based beverage for fermentation by two strains of lactic acid bacteria (LAB). Studies revealed that a procedure in which roasted brown rice and mungbean flour were mixed in proportion of 1:1, dispersed in cool water (15% w/v), filtered and added with amylolitic enzyme (0.2 ml of re-amylase and 0.05 of glucoamylase/100 ml) resulted in beverage most desirable for fermentation. The rice-based baverage was then inoculated with 4% culture of L bulgaricus or L acidophillus. Fermentation was carried out at an ambient temperature for 8, 16, 24, 32 and 40 hours. It was observed that L acidophillus grew almost the same with those of L bulgaricus. Lactic acid bacteria, titratable acidity and pH of fermented product varied from 20.5 x 1011 to 66 x 1019 CFU/ml, 0.46%-to-0.55% and 4.00-to-4.62, respectively. On the basis of these experiment, a process for the production of rice-based fermented beverage using L. acidophillus and 32-40 hrs of fermentation period was developed. Sensory evaluation showed that the product was well accepted when blended with 15% or 20% syrup.